2002
DOI: 10.1242/jcs.00119
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 differentially induces chemotaxis and DNA synthesis of human venous smooth muscle cells at the receptor-binding level

Abstract: Thrombospondin-1 is a large matricellular protein that acts as a pleiotropic growth factor for human vascular smooth muscle cells, and may play a role in the progression of vascular disease. Although we have previously demonstrated the dependence of both thrombospondin-1-stimulated cell chemotaxis and proliferation on tyrosine kinases, the receptor mechanisms involved remain obscure. This investigation aims to determine the nature of the receptor(s) involved in the cellular responses to thrombospondin-1. Cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…Our data indicates that TSP1 may have an additional anti-inflammatory activity through limiting inflammatory responses in VSMC. Our data suggests a role of TSP1 in internalization of microfibrils containing versican, but direct effects of TSP1 on VSMC signaling have been described (Isenberg et al, 2005;Lymn et al, 2002) and should also be considered in interpreting our results.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our data indicates that TSP1 may have an additional anti-inflammatory activity through limiting inflammatory responses in VSMC. Our data suggests a role of TSP1 in internalization of microfibrils containing versican, but direct effects of TSP1 on VSMC signaling have been described (Isenberg et al, 2005;Lymn et al, 2002) and should also be considered in interpreting our results.…”
Section: Discussionmentioning
confidence: 64%
“…The conformation of TSP1, therefore, may influence neointima formation through altering its interactions with versican and potentially other ECM components. However, TSP1 also interacts with several receptors on VSMC and thereby has direct effects on HASMC proliferation and migration (Isenberg et al, 2005;Lee et al, 2003;Lymn et al, 2002;Yabkowitz et al, 1993). Thus, TSP1 bound to versican on microfibrils may alter VSMC responses by providing prolonged stimulation of TSP1 receptors on these VSMC.…”
Section: Discussionmentioning
confidence: 99%
“…These similar or synergistic effects between the two sequences are consistent with their location in the three-dimensional structure of SPARC (27,38), a factor that could influence the effective concentrations of peptide required for bioactivity in different assays. The concentrations of peptides Z-1 to Z-3 used in this study are similar to those used recently on vascular cells for fragments of two proteins: the laminin ␥1 chain (a 12-mer at 0.1 mM) (39) and the type III Ca 2ϩ -binding repeat of thrombospondin 1 containing RGD (0.1 mM) (40), but are considerably less effective than a 17-mer derived from kininostatin, which inhibited endothelial cell migration to vitronectin at an IC 50 of 0.2 M (33). The study by Colman et al (33) also identified a second sequence within kininostatin (a 16-mer) that potently inhibited proliferation but not migration, and was also inhibitory in the CAM assay, results consistent with those reported here for peptide Z-1 (Fig.…”
Section: Fig 3 Major Fragments Produced By Proteolytic Cleavage Of mentioning
confidence: 95%
“…These interactions give rise to diverse endothelial cell responses. The integrins α3β1 and αvβ3, CD36, and CD47 similarly mediate distinct responses to TSP1 in vascular smooth muscle cells (VSMC) [18][19][20]. In platelets, CD36 and CD47 appear to be the major direct receptors for TSP1, although TSP1 binding to fibrinogen may also allow indirect binding to the major platelet integrin αIIbβ3 [21,22].…”
Section: Introductionmentioning
confidence: 99%